PERBANDINGAN SISTEM HUKUM INDONESIA DENGAN THAILAND TERKAIT LGBT DALAM PERSPEKTIF HUKUM POSITIF - Rizky Aulia; Aziza Aziz Rahmaningsih (Siyasah Jurnal Hukum Tatanegara, 2022)
In Indonesia, LGBT itself is still considered a very taboo subject. In the positive law of the Criminal Code, there is no LGBT legality. Indonesia is a country based on law, meaning that every action taken must be based on the law that regulates it. In the Criminal Code, it regulates material criminal acts in Indonesia. Criminal law is a whole set of rules that determine what actions are prohibited and included in criminal acts. Criminal rules related to same-sex relationships are regulated in Article 292 of the Criminal Code in the form of a threat of 5 years in prison and there is no legal regulation that explicitly regulates LGBT. Unlike the case with Thailand. Thailand is one of the countries that legalize same-sex marriage. The existence of the LGBT group in the country has received a response and tolerance from the community.